2019
DOI: 10.1073/pnas.1818759116
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of termite mounds

Abstract: Several species of millimetric-sized termites across Africa, Asia, Australia, and South America collectively construct large, meter-sized, porous mound structures that serve to regulate mound temperature, humidity, and gas concentrations. These mounds display varied yet distinctive morphologies that range widely in size and shape. To explain this morphological diversity, we introduce a mathematical model that couples environmental physics to insect behavior: The advection and diffusion of heat and pheromones t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…Group‐level patterns emerge from interacting individuals following simple behavioral rules. Theoretical studies have shown that the distinct patterns observed within and among species can emerge from quantitative variations of a single set of interaction rules (Bonabeau et al., 1998; Camazine et al., 2001; Franks et al., 1991; Karsai & Penzes, 1998; Khuong, Theraulaz, Jost, & Perna, 2011; Mizumoto, Kobayashi, & Matsuura, 2015; Ocko, Heyde, & Mahadevan, 2019; Theraulaz & Bonabeau, 1995). This parameter tuning mechanism allows for complex patterns to emerge from limited behavioral complexity at the individual level.…”
Section: The Emergence Of Diverse Patterns Through Self‐organization mentioning
confidence: 99%
See 2 more Smart Citations
“…Group‐level patterns emerge from interacting individuals following simple behavioral rules. Theoretical studies have shown that the distinct patterns observed within and among species can emerge from quantitative variations of a single set of interaction rules (Bonabeau et al., 1998; Camazine et al., 2001; Franks et al., 1991; Karsai & Penzes, 1998; Khuong, Theraulaz, Jost, & Perna, 2011; Mizumoto, Kobayashi, & Matsuura, 2015; Ocko, Heyde, & Mahadevan, 2019; Theraulaz & Bonabeau, 1995). This parameter tuning mechanism allows for complex patterns to emerge from limited behavioral complexity at the individual level.…”
Section: The Emergence Of Diverse Patterns Through Self‐organization mentioning
confidence: 99%
“…The cement pheromones attract workers to the construction sites, promoting further building and deposition of cement pheromones, thence exerting positive feedback (Grassé, 1959). This system has been mathematically modeled and simulated assuming that workers follow the abovementioned simple set of rules, and it was shown that the quantitative variations of associated parameters are sufficient to give rise to the multitude of nest structures observed in termites (Bonabeau et al., 1998; Mizumoto et al., 2015; Ocko et al., 2019). Local conditions influence the type of structures (e.g., pillars, walls, royal chamber, or shelter tubes) built by termites.…”
Section: The Emergence Of Diverse Patterns Through Self‐organization mentioning
confidence: 99%
See 1 more Smart Citation
“…Built precedents may trick practitioners into believing that thermal massing is a well-understood art [61]. However, a series of recent field studies on termite construction, which revealed that the coupling of mass and buoyancy is solely responsible for the thermal conditioning of some mounds [62][63][64][65], serve as a reminder that there is still much to learn.…”
Section: Thermal Massing For the Massesmentioning
confidence: 99%
“…Such structures are often surprisingly robust in noisy environments and their formation relies on the integration of regulatory processes on vastly different spatial scales of organisation, from the molecular level to tissue or population-level feedback (1). While historically theoretical and experimental research has focussed on the processes underlying the formation of complex structures (2)(3)(4), in recent years it has become clear that biological systems also have the remarkable capacity to break up and rebuild these structures (5). As an example, colonies of social insects rely on the robust specialisation of individuals into distinct castes, such as queen and worker polyphenisms (6).…”
Section: Introductionmentioning
confidence: 99%